Undelimited Maritime Areas: Obligations of States Under Article 74(3) and 83(3) of UNCLOS - Basir, Salawati Mat; Abd Aziz, Saidatul Nadia (UI Scholars Hub, 2020)
The delimitation of maritime areas between neighbors is of vital importance as it provides stable and long-lasting relations. Maritime boundary delimitation has been enriching the international law with a new chapter that has developed steadily in proportion with the related challenges and expectations. However, many maritime boundaries in the world are not delimited. This implies that disputes relating to maritime delimitation have many issues in future. In this case, State shall have to negotiate among them or to use dispute resolution mechanism. Under Article 74 and Article 83 of the United Nations Convention on the Law of the Sea (UNCLOS) provides for the delimitation of the territorial sea, the continental shelf and the economic exclusive zone. However, maritime delimitation disputes reveal that these provisions hardly occupy the central place they are expected to. This paper examines the issue of undelimited maritime areas where involved the Article 74(3) and Article 83(3) of UNCLOS and of vital importance in that it provides for stable and long-lasting relations among States.